Caracterização de solos sob diferentes usos na região sul do Amazonas - Oliveira, Ivanildo Amorim De; Campos, Milton César Costa; Freitas, Ludmila De; Soares, Marcelo Dayron Rodrigues (Instituto Nacional de Pesquisas da Amazônia, 2015)
Areas with native vegetation are increasingly fragmented due to agricultural occupation, and with the removal of the natural vegetation, the use of soil has shown changes in their chemical, physical and biological attributes. Thus, the objective of this work was to evaluate soil physical and chemical attributes using multivariate technique. The study was carried out in area with Archaeological Black Earth (TPA), forest, pasture, agroforestry, sugar cane and cassava. In these areas 64 soil samples were collected from disturbed and undisturbed soils at a regular spacing of 10 meters and 0.0 to 0.10 m depth for chemical and physical analyses. Areas of TPA and agroforestry had different values for physical and chemical attributes in comparison with soils from pasture, forest, cassava and sugar cane. The areas cultivated with cassava, sugar cane and pasture had similar physical and chemical characteristics. The use of the multivariate analysis tool proved to be useful to detect similarities or differences in soils attributes based on chemical and physical in the study area.

Áreas com vegetação nativa são cada vez mais fragmentadas devido ao desmatamento associado à atividade agropecuária, o que provoca alterações nos atributos químicos, físicos e biológicos do solo. Assim, o objetivo do estudo foi avaliar os atributos físicos e químicos do solo por meio de técnicas estatísticas multivariadas. O estudo foi realizado em áreas de terra preta arqueológica (TPA), floresta, pastagem, agrofloresta, cana-de-açúcar e mandioca. Nestas áreas foram coletadas 64 amostras de solos deformadas e indeformadas com espaçamento regular de 10 m na profundidade de 0,0-0,10 m para determinação dos atributos químicos e físicos. O estudo mostra que as áreas com TPA e agrofloresta apresentaram valores de atributos físicos e químicos diferentes da pastagem, floresta, mandioca e cana-de-açúcar. Por serem ambientes cultivados, as áreas de mandioca, cana-de-açúcar e pastagem apresentam características físicas e químicas similares. O uso das técnicas de análises multivariadas foi eficiente para verificar as similaridades ou as diferenças, com base nos atributos químicos e físicos do solo em cada área estudada.
Characterization of soils under different land uses in the southern region of the Amazonas
Keywords: análise multivariada; componente principal; solos da Amazônia; terra preta arqueológica; multivariate analysis; principal component; Amazonian of soils; archaeological black earth